Analisis Korelasi Tingkat Absensi dengan Hasil Belajar Siswa MTs. Sains al-Gebra Kota Sorong Papua Barat - Agus Yudiawan (LPPM IAIN Sorong, 2019)
Poor attendance (absenteeism) is associated with low academic achievement. A teacher not only assesses student achievement based solely on grades obtained through tests or exams but also assesses one of which comes from student attendance. Students who diligently entered to give a positive value in the assessment and vice versa, if rarely entered it will have a negative impact on learning outcomes. The study aims to determine and prove the relationship of absenteeism with learning outcomes in MTs. Sains Al Gebra Kota Sorong. This research uses quantitative approach with population of 67 people. The sampling technique used a census sample with all members of the population sampled. The data were collected by collecting documents in the form of learning grade and class abscess scores. Data analysis uses product moment correlation with 95% confidence level. The results showed that there is a strong and opposite relationship between absenteeism and student learning outcomes. The conclusion obtained is the greater the absence of students (absenteeism), the lower the students' learning outcomes and vice versa.